Interference of Thai Language on Dialectal Variations of Jawi Malay in Narathiwat - Rambe, Indra Hadinata; Sohnui, Suhailee; Khairunnisah, Khairunnisah; Hasibuan, Nikmah Sari; Harahap, Eli Marlina (JOLLT Journal of Languages and Language Teaching, 2024)
The connection between language and culture becomes increasingly evident when the Thai language influences the variations of Jawi Malay dialects in Narathiwat. This research aims to analyze the impact of Thai language interference on the dialectal variations of Malay language in Narathiwat, Thailand, using a sociolinguistic approach. We investigate changes in language, including vocabulary usage, phonological shifts, and social influences in the everyday situations of Narathiwat society. The research methods involve interviews, surveys, text analysis, and observations in everyday contexts. The expected outcomes are to enhance understanding of language dynamics in Narathiwat, which plays a crucial role in preserving cultural and linguistic identities in a multilingual environment. This study has the potential to provide valuable insights into the preservation and maintenance of Malay language in Narathiwat, emphasizing the importance of language and sociolinguistic research in areas with strong language influences and significant cultural blends. This abstract covers the research background, objectives, research methods, research findings, discussion, conclusion, and research implications, ensuring a comprehensive understanding of the scope and relevance of this study